2020
DOI: 10.1007/s00429-020-02113-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intelligence from brain gray matter volume

Abstract: A positive association between brain size and intelligence is firmly established, but whether region-specific anatomical differences contribute to general intelligence remains an open question. Results from voxel-based morphometry (VBM)one of the most widely used morphometric methods-have remained inconclusive so far. Here, we applied cross-validated machine learning-based predictive modeling to test whether out-of-sample prediction of individual intelligence scores is possible on the basis of voxel-wise gray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 79 publications
(129 reference statements)
4
42
0
Order By: Relevance
“…The brain regions implicated in better cognitive performance in the chimpanzees in the current study included regions within the middle and inferior frontal gyri, supramarginal, and angulargyrus, and the cerebellum. In humans, similar brain regions have been reported to be associated with general intelligence or "g" (Haier et al, 2004(Haier et al, , 2010Hilger et al, 2020;Hogan et al, 2011), suggesting some homology in brain regions implicated in general cognitive functions between humans and chimpanzees. Similarly, the findings reported here are consistent with a previous study in a subset of these chimpanzees that showed that increasing cognitive performance as assessed by the PCTB was associated with larger brain volumes and increased cortical thickness (Hopkins, Li, et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…The brain regions implicated in better cognitive performance in the chimpanzees in the current study included regions within the middle and inferior frontal gyri, supramarginal, and angulargyrus, and the cerebellum. In humans, similar brain regions have been reported to be associated with general intelligence or "g" (Haier et al, 2004(Haier et al, , 2010Hilger et al, 2020;Hogan et al, 2011), suggesting some homology in brain regions implicated in general cognitive functions between humans and chimpanzees. Similarly, the findings reported here are consistent with a previous study in a subset of these chimpanzees that showed that increasing cognitive performance as assessed by the PCTB was associated with larger brain volumes and increased cortical thickness (Hopkins, Li, et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…Inter-voxel predictors appear in 2 (7%) studies (Powell et al 2017;Zhang et al 2019), in the form of local dMRI structural connectivity. Intra-voxel predictors appear in 5 (17%) studies (Hilger et al 2020;Jiang et al 2020b;Kong et al 2019;Li et al 2018;Wu et al 2020) From the 30 studies encompassed in this review, 9 did not directly mention the tests used (Dadi et al 2019;Dryburgh et al 2020;He et al 2020;Kashyap et al 2019;Kong et al 2019;Li et al 2019;Wang et al 2015;Wu et al 2020;Yoo et al 2019). Supplementary materials and citations were consulted to identify tests used in all but one study (Dryburgh et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…There was, however, little information about the measurement's validity for the populations under study. 3 studies cited references deemed adequate (Ferguson et al 2017;Wei et al 2020;Yang et al 2019), whereas partial references were cited in 2 studies (Hilger et al 2020;Lin et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Our results of significantly decreased total volume of GMV and WMV in ID compared to HC are in accordance with previous findings ( 14 , 20 , 28 30 ). The higher GMV and WMV in HC are mainly related to a larger number of neuron cells and fibers for better computational and communicational ability ( 31 ). Although most mature processes of the brain are completed before age 2 years like shape, volume, and fold, and the brain size reaches about 90% of adult size by 5 years of age, it keeps plasticity across the lifespan ( 32 ).…”
Section: Discussionmentioning
confidence: 99%